Active Power Filter Based Optimum Design Of PI Controller Using Particle Swarm Optimization Method - Thajeel, Ekhlas Mhawi; M. H., Sulaiman; Hamdan, Daniyal (UM Power Energy Dedicated Advanced Centre (UMPEDAC), 2015)
This paper proposes an optimal design method for Shunt Active power filter (SAPF). An active harmonic filter is used to eliminate current harmonics caused by nonlinear loads. The current control strategy utilizes Synchronous Reference Frame method to improve power quality through compensating harmonics and reactive power required by a nonlinear load. The power quality standard IEEE-519 states that the total harmonic distortion (THD) caused by electrical equipment gear should be within the agreeable range of 5%. This study is conducted to investigate the utilization of Particle Swarm Optimization (PSO) in optimizing PI controller for SAPF’s DC link voltage. The simulation model of the overall system is developed in MATLAB/Simulink environment. From analysis, it has been found that PSO technique proves to be effective in reducing the THD of the source current.